Advances in proteomic techniques for biomarker discovery in COPD. (January 2011) - Casado, Begoña; Luisetti, Maurizio; Iadarola, Paolo
Chronic obstructive pulmonary disease (COPD) is a disorder characterized by chronic inflammation of the lung with airflow obstruction and progressive deterioration of pulmonary function. The need to discover and validate biomarkers as prognostic tools of development and progression of the disease has received further support with the advent of proteomic techniques. Liquid chromatography–mass spectrometry (LC/MS) and gel electrophoresis–mass spectrometry (2-DE/MS) have been applied to investigate the proteome of a number of lung-origin samples, including sputum, bronchoalveolar lavage fluid, exhaled-breath condensate, cells and biopsies from COPD patients. In particular, 2-DE and MS are the main proteomic approaches with 2-DE presenting the major approach for quantitative proteomics. The molecules identified as potential biomarkers of COPD may represent a preliminary step for better comprehension of the mechanisms involved in the onset/progression of the disease.